Virtual Learning : a revolutionary approach to building a highly skilled workforce - Schank, Roger (Mc Graw Hill New YorkUS, 1997)
Proposes the use of computer simulations and role-playing scenarios in training programmes, as the practical, cost effective alternative to apprenticeships and on-the-job training programmes that utilise lectures, tests, memorization and manuals. Opines that there should be a nexus between organizational training principles and the principles of how the mind works and how learning occurs. Provides virtual training techniques and itemises the steps for starting a training revolution.